Solution‐Phase Chemical Synthesis of Modified RNA Dinucleotides. Issue 11 (7th November 2022) - Senthilvelan, Annamalai; Shanmugasundaram, Muthian; Kore, Anilkumar R.
Abstract: This article describes a simple, reliable, efficient, and improved solution‐phase method for the gram‐scale chemical synthesis of RNA dinucleotides such as pAm pA, pAm pG, and pAm pU that utilizes phosphoramidite chemistry. The overall synthetic strategy involves three steps. The first step involves the coupling reaction between 5′‐ O ‐MMT protected nucleoside‐3′‐ O ‐phosphoramidite and a protected nucleoside containing a free 5′‐OH group in the presence of tetrazole, followed by the oxidation of phosphite triester using tert ‐butyl hydroperoxide to give the corresponding protected Nm pN. Next, the 5′‐ O ‐MMT is cleaved under 3% trichloroacetic acid in dichloromethane conditions. Finally, the 5′‐hydroxyl group is phosphorylated by the use of an activated bis(2‐cyanoethyl)‐ N, N ‐diisopropyl phosphoramidite using tetrazole, followed by the oxidation of trivalent to pentavalent phosphorus using tert ‐butyl hydroperoxide and subsequent deprotection using ammonium hydroxide to afford the corresponding RNA dinucleotide, pNm pN, in good yields with high purity (>99.5%). © 2022 Wiley Periodicals LLC.